How useful are interpretation aids for communicating large-scale assessment results to teachers? - Ludewig, Ulrich; Becher, Laura; McElvany, Nele (Frontiers in Education, 2025)
Large-scale assessments (LSAs) significantly influence educational policy and perceptions of inequality, extending their impact beyond researchers to educators. LSAs predominantly utilize standard deviation units, supplemented by interpretation aids to enhance result comprehension. This pre-registered research delves into the utility of interpretation aids for teachers and their potential to influence result interpretation. The study used an experimental study design with N = 75 in teachers evaluating the usefulness and perceived relevance of several LSA reporting vignettes. Findings indicate that while all interpretation aids surpass standard deviation units in perceived usefulness, they also slightly alter the perceived magnitude of differences. The study underscores the importance of portraying interpretation aids as supplementary tools for context and reference, rather than replacements for statistics. Effective communication strategies should integrate interpretation aids to enrich understanding without overshadowing statistical significance. This approach ensures educators can leverage LSAs for informed decision-making while maintaining fidelity to statistical rigor.